Über bibliographische Arbeit in der Entomologie. - Köppen, Herbert (Contributions to Entomology = Beiträge zur Entomologie, 1968)
Scientific progress entails a rapid increase in the number of publications, which creates special problems of the principles of methods and economy of scientific work for authors and editors as well as users and persons employed in the evaluation of publications. Possibilities of solving these urgent problems in bibliographical work are studied. Aims and purposes of scientific bibliography have changed. The traditional method of quantitative compilations covering vast fields is increasingly replaced by qualitatively selective principles for analytical surveys of specialized subjects. This is intended to improve the efficiency of scientific work.